Outcome of neoadjuvant treatment for pancreatic cancer in elderly patients: comparative, observational cohort study. Issue 8 (22nd June 2021) - Oba, A; Wu, Y H A; Lieu, C H; Meguid, C; Colborn, K L; Beaty, L; Al-Musawi, M H; Davis, S L; Leal, A D; Purcell, T; King, G; Wooten, E S; et al.
Abstract: Background: Use of neoadjuvant therapy for elderly patients with pancreatic cancer has been debatable. With FOLFIRINOX (folinic acid, 5-fluorouracil, irinotecan, oxaliplatin) or gemcitabine plus nab-paclitaxel (GnP) showing tremendous effects in improving the overall survival of patients with borderline resectable and locally advanced pancreatic cancer, there is no definitive consensus regarding the use of this regimen in the elderly. Methods: This study evaluated the eligibility of elderly patients with borderline resectable or locally advanced pancreatic cancer for neoadjuvant therapy. Patients registered in the database of pancreatic cancer at the University of Colorado Cancer Center, who underwent neoadjuvant treatment between January 2011 and March 2019, were separated into three age groups (less than 70, 70–74, 75 or more years) and respective treatment outcomes were compared. Results: The study included 246 patients with pancreatic cancer who underwent neoadjuvant treatment, of whom 154 and 71 received chemotherapy with FOLFIRINOX and GnP respectively. Among these 225 patients, 155 were younger than 70 years, 36 were aged 70–74 years, and 34 were aged 75 years or older. Patients under 70 years old received FOLFIRINOX most frequently (124 of 155 versus 18 of 36 aged 70–74 years, and 12 of 34 aged 75 years or more; P  < 0.001). Resectability was similar among the three groups (60.0, 58.3, and 55.9 per cent respectively; P  = 0.919). Trends towards shorter survival were observed in the elderly (median overall survival time 23.6, 18.0, and 17.6 months for patients aged less than 70, 70–74, and 75 or more years respectively; P  = 0.090). After adjusting for co-variables, age was not a significant predictive factor. Conclusion: The safety and efficacy of multiagent chemotherapy in patients aged 75 years or over were similar to those in younger patients. Modern multiagent regimens could be a safe and viable treatment option for clinically fit patients aged at least 75 years. Abstract : The safety and efficacy of multiagent chemotherapy for pancreatic cancer were similar in patients aged 75 or more and their younger counterparts. Given the fact that age was not an independent prognostic factor, modern multiagent regimens could be a safe and viable treatment option for clinically fit patients aged 75 years or older.